The Relationship Between The Orientation Towards Social Marketing And The Organizational Culture In Banks - عمار قصي; حلوم سنان; محمد بسام (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The aim of this research is to demonstrate the relationship between the orientation towards adopting social marketing in its dimensions (customer satisfaction, customer confidence, social dealings, and social contribution) and the organizational culture in commercial banks operating in Latakia Governorate. The researcher relied on the descriptive and analytical approach, in order to describe the research variables and analyze them based on the primary data that was collected. The researcher conducted a field study on commercial banks operating in Latakia Governorate to collect the necessary initial data. One of the most important results of this study was that the correlation coefficient between the dimensions of social marketing and organizational culture was 0.799, and this indicates that there is a good correlation between the dimensions of social marketing and organizational culture, and that banks focus on serving customers well, pay attention to customer complaints and suggestions, and make customers feel their distinguished role in their plans. The banks subject to study contribute socially well by preserving the environment, supporting the local community, and supporting local activities. On the other hand, the banks subject to study enjoy an organizational culture characterized by collective participation and the promotion of the values ​​of justice among workers and an organizational environment that helps supporting the psychological needs of workers.